LCA of virgin and recycled materials to assess the sustainability of paved surfaces in agricultural environment. (20th March 2023) - Santolini, Enrica; Bovo, Marco; Barbaresi, Alberto; Torreggiani, Daniele; Tassinari, Patrizia
Abstract: The construction sector is currently characterized by high raw material consumption but also by the production of high volume of wastes, mostly constituted by construction and demolition wastes that could be valorized promoting the use of recycled aggregates in substitution of raw aggregates. A promising application for recycled aggregates is for the realization of rural roads and pavements. The agricultural context, characterized by particular type of traffic and need to balance performance and integration with the environment, is suited for the use of these materials for paved surfaces since it can promote, in several cases, the adoption of rural circular processes internal to the farm. However, if on one hand the adoption of recycled aggregates could increase the sustainability of the sector, on the other it could increment the environmental loads if the whole process is not properly organized. For instance, the negative effects of transportation operations can cancel the environmental benefits if high distances between the production and the destination sites are present. This work reports the results of the Life Cycle Assessment (LCA), from cradle-to-gate, of four different construction aggregate classes that can be used for the realization of rural roads, pavements and forecourts, and paved areas in agricultural environment. The first three materials are recycled aggregates produced by the recycling processes of construction and demolition waste and the fourth type refers to gravel aggregates produced from natural resources. The Life Cycle Assessment was realized using site-specific primary data from the local territorial context and paying particular attention to transportation-related impacts, land use, avoided landfill and preservation of non-renewable resources. The results of the work clearly show that the environmental impacts in both scenarios of recycled aggregates are lower than the virgin aggregate scenario. In fact, considering the midpoint categories, the recycled materials proved to be more virtuous in almost all the indicators, with the exception of the marine eutrophication. The most significant gap between virgin and recycled materials has been in global warming and marine and freshwater eco-toxicity. Highlights: C&DW disposed in landfills rise the ecological footprint of the construction sector. Life cycle assessment of recycled aggregates of an Italian plant has been performed. Recycled aggregates are a valuable resource also for the agricultural context. Comparison on environmental impact of virgin and recycled aggregates was realized. Recycled aggregates show a considerable reduction of the environmental impacts.